Biologic responses of rice field crab Esanthelphusa nani (Naiyanetr, 1984) to herbicides in paddy fields, Nan province - Rachata Maneein (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012